2017
DOI: 10.22159/ajpcr.2017.v10i2.15917
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Female Workers From a Textile Mill: Effect of Noise

Abstract: Objective: Noise creates alteration in human health in both physical as well as psychological variations. Effect of noise on components of metabolic syndrome (MetS) has been discussed but not well established. The aim of this study was to investigate the MetS in female workers from textile mill.Methods: A total of 65 female workers were recruited for the study from the high noise (>70 dB) area and low noise (<40 dB) area of a textile mill. Body mass index (BMI), blood pressure (BP), blood sugar (BS), and lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Twenty studies were identified that reported on the impact of noise exposure on cholesterol levels [Table S9] 36 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ]; however, many of them ( n = 13) are reported narratively in the summary of findings table based on differences in populations, measurement of exposures, measurement of outcome, and reporting of outcomes. [ 45 46 47 50 52 53 55 56 58 59 60 61 62 ] Concerns with risk of bias due to confounding, exposure assessment, missing data, and measurement of outcomes were identified [Table S10].…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies were identified that reported on the impact of noise exposure on cholesterol levels [Table S9] 36 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ]; however, many of them ( n = 13) are reported narratively in the summary of findings table based on differences in populations, measurement of exposures, measurement of outcome, and reporting of outcomes. [ 45 46 47 50 52 53 55 56 58 59 60 61 62 ] Concerns with risk of bias due to confounding, exposure assessment, missing data, and measurement of outcomes were identified [Table S10].…”
Section: R Esultsmentioning
confidence: 99%
“…Eight studies examined the relationship between occupational noise and cholesterol. [ 36 44 48 49 51 54 56 57 ] Among cohort studies, it was found that occupational noise over 75 dBA (versus ≤75 dBA) may have little to no effect on cholesterol (MD: 2.43; 95% CI: −7.02–11.89); however, the evidence was very uncertain due to concerns with risk of bias and imprecision [ Table 4 ]. Similarly, among the cross-sectional studies, it was found that occupational noise over ≥80 dBA (versus <80 dBA) may have little to no effect on cholesterol (MD: 4.54; 95% CI: −5.03–14.12) [ Figure 3 ]; however, the certainty in the evidence was very low due to concerns with risk of bias, imprecision, and inconsistency [ Table 4 ].…”
Section: R Esultsmentioning
confidence: 99%
“…A total of 78 studies were identified that reported on the impact of noise exposure on blood pressure [Table S5],[ 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 ] including two studies evaluating children from ages 3 to 7 ye...…”
Section: R Esultsmentioning
confidence: 99%
“…There were 27 studies identified that examined the relationship between occupational noise and blood pressure. [ 24 25 26 27 36 37 42 44 47 48 53 54 58 59 60 64 68 73 78 82 84 85 87 88 89 90 97 ] Among cross-sectional studies ( n = 15), for studies that reported on exposure continuously, a 10-dBA increase in occupational noise was found to have little to no effect on blood pressure (MD: 0.14, 95% CI: 0, 0.28; MD: 0.23, 95% CI: 0, 0.45; for systolic and diastolic blood pressure, respectively; very low CoE) [ Figure 6 A]. For studies that reported occupational noise in categories, it was found that higher levels of occupational noise (≥85 dBA vs <85 dBA) may increase systolic blood pressure and diastolic blood pressure (MD: 5.26, 95% CI: 2.23, 8.29; MD: 3.31, 95% CI: 0.70, 5.92; for systolic and diastolic blood pressure, respectively; very low CoE).…”
Section: R Esultsmentioning
confidence: 99%